The United Nations World Water Development Report 2018 - United Nations Educational, Scientific; Cultural Organization (United Nations, 2019)
The 2018 edition of the World Water Development Report seeks to inform policy and decision-makers, inside and outside the water community, about the potential of nature-based solutions (NBS) to address contemporary water management challenges across all sectors, and particularly regarding water for agriculture, sustainable cities, disaster risk reduction and water quality. Water management remains heavily dominated by traditional, human-built (i.e. ‘grey’) infrastructure and the enormous potential for NBS remains under-utilized. NBS include green infrastructure that can substitute, augment or work in parallel with grey infrastructure in a cost-effective manner. The goal is to find the most appropriate blend of green and grey investments to maximize benefits and system efficiency while minimizing costs and trade-offs.NBS for water are central to achieving the 2030 Agenda for Sustainable Development because they also generate social, economic and environmental co-benefits, including human health and livelihoods, food and energy security, sustainable economic growth, decent jobs, ecosystem rehabilitation and maintenance, and biodiversity. Although NBS are not a panacea, they will play an essential role towards the circular economy and in building a more equitable future for all.